Policies Towards Baduy Tribe and its Impacts: A Brief Review - Puguh Toko Arisanto (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
The Baduy tribe is an indigenous community in Banten Province divided into two main groups, namely Inner Baduy and Outer Baduy, with varying levels of adherence to customary law and exposure to modernization. This article examines various government policies that affect the survival and identity of the Baduy tribe. These policies include the recognition of customary rights through Lebak Regency Regulation No. 32 of 2001, the designation of Kanekes Village as customary land, and the designation of the Baduy area as a tourist destination. Although these policies aim to protect the rights and preserve the culture of the Baduy, their implementation has created a dilemma. On the one hand, tourism opens up new economic opportunities and raises cultural awareness. On the other hand, the influx of tourists triggers significant social, cultural, economic, and environmental changes, especially among the Outer Baduy, including the adoption of modern technology, shifts in consumption patterns, and increased environmental pollution. Thus, preservation policies have ironically become drivers of change that undermine the Baduy community's original identity.